Polar lakes and rivers limnology of Arctic and Antarctic aquatic ecosystems - Vincent, Warwick F.; Laybourn-Parry, Johanna (Oxford : Oxford University Press, 2008)
This title provides an overview of the ecology of high latitude lakes, rivers and glacial environments in both the North and South polar regions. It describes each ecosystem type, the remarkable aquatic life that thrives in these extreme habitats and the similarities and differences between Arctic and Antarctic waters.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Freshwater biology -- Polar regions; Lake ecology -- Polar regions; Stream ecology -- Polar regions